The main approaches to the development of innovative pharmaceutical industry of the Russian Federation in the context of globalization - Klunko, Natalia; Reta, Marynia (Central Bohemia University, 2011)
Pharmaceutical industry - one of the few areasin which innovations affect all of us, because ultimately have a direct impact on the duration and quality of life for us and our loved ones. In the presence of a strong market and a lack of understanding of the need for innovation is necessary, in our opinion, investing in basic research and facilitate the process of innovation in the pharmaceutical industry by the state and society. For the targeted development of pharmaceutical industry seems appropriate to determine at the state level prospects for the domestic pharmaceutical industry and its role in the international market, and develop a drug "doctrine" of Russia. This paper analyzed the problems of the state associated with the pharmaceutical market in the globalization period. Also investigated the theoretical aspects of the modern study of globalization in the light of the analysis for the global pharmaceutical industry and analyzes the major political and economic factors that have the most significant impact on the production of pharmaceuticals.
Keywords: pharmaceutical industry; pharmaceutical market; period of globalization; production of pharmaceuticals; process of drug development